Esophageal and Cardia Cancer: statiscal analysis - Lerena, Ana; Ricciardi, Norma; Voelker, Ricardo; Balboa, Oscar; Praderi, Luis A (Cirugía del Uruguay, 1980)
A serial of 168 esophageal and cardia cancer is analized. The predominance of middle portien 1o·calization is pointed out. Resection as the best palliative procedure is considered. In cancer localized in middle and lower section, transit reconstruction was performed in one stage, following Sweet or Lewis tecnic. In upper sectio'n, esophageal - colonic anastomosis was performed in one stage.